2001
DOI: 10.1128/aac.45.4.1287-1291.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Activities of Amikacin, Cefepime, Amikacin plus Cefepime, and Imipenem against an SHV-5 Extended-Spectrum β-Lactamase-Producing Klebsiella pneumoniae Strain

Abstract: The in vitro and in vivo effectiveness of amikacin, cefepime, and imipenem was studied using a high inoculum of an extended-spectrum ␤-lactamase-producing Klebsiella pneumoniae strain. An in vitro susceptibility test at the standard inoculum predicted the in vivo outcome of amikacin or imipenem while it did not do so for cefepime due to the inoculum effect.Extended-spectrum ␤-lactamase (ESBL) production is one of the main mechanisms of resistance to ␤-lactam antibiotics among the strains of the family Enteroba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
(32 reference statements)
2
18
0
Order By: Relevance
“…However, inoculum effects in ESBL-producing Klebsiella spp. have been reported for cefepime both in vitro and in vivo (12,29), and they could be due, at least in part, to the hydrolysis of this drug by ESBLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inoculum effects in ESBL-producing Klebsiella spp. have been reported for cefepime both in vitro and in vivo (12,29), and they could be due, at least in part, to the hydrolysis of this drug by ESBLs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that an increase in inoculum size can be correlated with an increase in ␤-lactam MICs and a decrease in efficacy in vivo (11,12,29,30). Factors that could contribute to these effects are the number, type, and amount of ␤-lactamases; outer membrane permeability; efflux; number and susceptibility of penicillin-binding protein targets; and phase of growth.…”
Section: Discussionmentioning
confidence: 99%
“…This so called "inoculum effect, " in which drug MICs increase dramatically in the presence of an increased bacterial load despite apparent initial susceptibility, has been observed in both in vitro and animal studies [25][26][27][28][29][30][31]. Highlighting one experience, Burgess and colleagues evaluated cefepime and meropenem against standard-and high-inoculum ESBL Klebsiella pneumoniae infections [32].…”
Section: Cefepimementioning
confidence: 99%
“…In our previous study, human serum levels of other renally excreted drugs, amikacin and imipenem, could be approximated using 18 mg/kg of cisplatin pretreatment and by a slightly more frequent administration than in humans (Szabó et al 2001). We suggest that human serum levels can be achieved in animal experiments with the use of cisplatin pretreatment without labour-intensive procedures.…”
Section: Discussionmentioning
confidence: 97%